APPRAISAL OF MANREGA IN THE RURAL AREAS OF MUZAFFARPUR DISTRICT - ABHAY RANJAN (International Journal of Multidisciplinary Research and Studies, 2020)
The Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) is regarded as a "Silver Bullet" for the elimination of rural poverty and unemployment since it creates a demand for productive labour force in rural areas. It provides an alternative means of subsistence, which has the potential to reduce migration, limit the employment of children, alleviate poverty, and enable rural communities to become self-sufficient through the development of productive assets, such as the building of roads, the cleaning of water tanks, and the preservation of soil and water, among other things. These benefits have the potential to reduce migration, limit the employment of children, alleviate poverty, and enable rural communities to become self-sufficient. As a consequence of this, it has been referred to as the anti-poverty project that is the most comprehensive in the entirety of the entire world. However, the success of this Act is dependent on it being implemented in the suitable manner in order for it to be successful. As a result, the objective of this research is to carry out an in-depth examination of the steps involved in the execution of this programme as well as the effects that the programme has had on the means of subsistence utilised by tribal communities. To be more specific, the question that will be investigated is to what extent the MGNREGS has done justice in sustaining the livelihoods of low-income tribal communities in a panchayat that is dominated by tribal people in the district of Muzaffarpur in the state of Bihar. This panchayat is located in the Muzaffarpur region of Bihar.